2015
DOI: 10.1080/15384101.2014.998067
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib inhibits BTK-driven NF-κB p65 activity to overcome bortezomib-resistance in multiple myeloma

Abstract: Abbreviations: MM -multiple myeloma; PI -proteasome inhibitor; NF-kB -nuclear factor-kappa B; BMSC -bone marrow stromal cells; BTK -Bruton's tyrosine kinase.Multiple Myeloma (MM) is a haematologic malignancy characterized by the accumulation of clonal plasma cells in the bone marrow. Over the last 10-15 y the introduction of the proteasome-inhibitor bortezomib has improved MM prognosis, however relapse due to bortezomib-resistance is inevitable and the disease, at present, remains incurable. To model bortezomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 43 publications
(69 reference statements)
2
54
1
1
Order By: Relevance
“…Higher NF-kb expression is seen in bortezomib refractory primary MM patients 18 and bortezomib resistance in MM is associated with increased basal nuclear localization of NF-kb p65 in bortezomib-resistant myeloma cells. 13 Here, we also show increased nuclear NF-kb p65 levels in bortezomib-resistant U266 cells compared to the parent counterpart. We showed that TrxR1 inhibition using auranofin reduced NF-kb p65 mRNA and protein expression, reduced the mRNA levels of downstream NF-kb-regulated genes including anti-apoptotic and proliferation genes in bortezomib-resistant U266 cells (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Higher NF-kb expression is seen in bortezomib refractory primary MM patients 18 and bortezomib resistance in MM is associated with increased basal nuclear localization of NF-kb p65 in bortezomib-resistant myeloma cells. 13 Here, we also show increased nuclear NF-kb p65 levels in bortezomib-resistant U266 cells compared to the parent counterpart. We showed that TrxR1 inhibition using auranofin reduced NF-kb p65 mRNA and protein expression, reduced the mRNA levels of downstream NF-kb-regulated genes including anti-apoptotic and proliferation genes in bortezomib-resistant U266 cells (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Increased nuclear p65 protein levels have been correlated with the acquisition of drug resistance in cancer cells. 13,29 Our results showed that auranofin-induced TrxR1 inhibition reduced the hypoxia-induced nuclear accumulation of NF-kb p65 protein, reduced the mRNA levels of p65 and downstream NF-kb-regulated genes, Survivin and Cyclin D1 (Fig. 3).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations